Pemberdayaan Masyarakat dalam Perlindungan Mata Air di Desa Adat Sibetan, Karangasem, Bali - Kadek Windy Candrayana (Universitas Warmadewa, 2024)
In addition to its benefits as a means of fulfilling water needs, springs in Bali Province also play a role in religious activities in Bali. Religious rituals that utilize springs as a means are melukat. Melukat is a self-cleansing ritual that is currently popular as religious tourism offered by several spring areas in Bali. Yeh Jepun Spring located in Sibetan Village is used as a source of clean water for the surrounding community. The condition of the spring is currently threatened by flooding that occurs in the river so spring protection is needed. This activity is carried out by designing protection and arrangement of springs to be able to provide added value to the spring area. The implementation of the activity begins with the implementation of a survey in the form of a topographic survey, discharge measurement survey, and water quality testing. The results of this activity are embankments surrounding the spring, spring boundaries and the arrangement of springs.